The truants - Weinberg, Kate (G.P. Putnam & Sons, 2020)
Jess Walker has come to a concrete campus under the flat gray skies of East Anglia for one reason: to be taught by the mesmerizing and rebellious Dr. Lorna Clay, whose seminars soon transform Jess's thinking on life, love, and Agatha Christie. Swept up in Lorna's thrall, Jess falls in with a tightly knit group of rule-breakers--Alec, a courageous South African journalist with a nihilistic streak; Georgie, a seductive, pill-popping aristocrat; and Nick, a handsome geologist with layers of his own. But the dynamic between the friends begins to darken, until a tragedy shatters their friendships and love affairs, and reveals a terrible secret. Soon Jess must face the question she fears most: what is the true cost of an extraordinary life?